RECUPERAÇÃO DE ÁREA DEGRADADA E MONITORAMENTO NO PARQUE MUNICIPAL NATURAL LAGOA COMPRIDA - MELO, Rafael Alves Ferreira de Melo; POMPEU, Patrícia Vieira; IBANEZ, Fernando Martins 3 (fimquelonio@hotmail.com) (ANAIS DO ENIC, 2023)
-